Evolution of postural control assessment: From dynamic posturography to virtual reality - Keshner, Emily A.; Mallinson, Arthur I.; Longridge, Neil S.; Sinno, Solara; Petersen, Hannes; Perrin, Philippe (Frontiers in Neurology, 2023)
During the early years of spaceflight it was documented that astronauts were impaired and incapacitated upon return to earth. Computerized Dynamic Posturography (CDP) was devised to investigate and quantify this deficit, and eventually progressed into a clinical assessment tool. The current sprouting of virtual reality (VR) technologies has allowed for the development of an alternative approach that could be more informative. Many low-cost VR systems (including desktop gaming programs designed for rehabilitation) are now available. Continued improvements in this technology indicate a high probability that VR will become an integral component of posturography by replacing present mechanical CDP techniques. We researched the relevant literature to evaluate the strengths and weaknesses of CDP using the Equitest (Neurocom International; Clackamas USA), and the added benefits of incorporating VR to help clinicians assess the complex task of balance maintenance. VR is capable of manipulating task and environmental demands in order to assess functional postural behavior. VR is also a useful tool for clinical testing of postural disorders resulting from sensory mismatch. Although posturography is still a useful clinical tool, VR provides an inherent conflict between the visual and vestibular senses and can elevate the effectiveness of CDP for both assessment and intervention. We conclude that, when initially developed, CDP was innovative and ahead of its time. However, with the advent of VR, we have a chance to modernize CDP and enhance its value as a clinical instrument.